Killing, Capture, Trade and Ape Conservation - Foundation, Arcus (Life Sciences, 2021)
This fourth volume analyses significant threats to the long-term survival of wild ape populations. The chapters bring together original research and analysis with topical case studies and emerging best practices to further the ape conservation agenda around killing, capture and trade. This title is also available as Open Access via Cambridge Core.